Effects of Xiangshao granules on clinical symptoms and serum hormone levels of menopausal syndrome: a systematic review and meta-analysis of randomized controlled trials - Tang, Xing; Wang, Chengcheng; Liu, Yang; Xu, Yisha; Dong, Shoujin; Dai, Min; Li, Chunmei; Zhai, Yan; Lan, Shoujen; Yen, Yeayin; Wang, Chao; Yu, Congcong (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the efficacy and safety of Xiangshao granules in improving clinical symptoms and regulating serum hormone levels in patients with menopausal syndrome (MPS).MethodsThis study was developed according to the PRISMA 2020 guidelines. Eight databases including PubMed, Web of Science, The Cochrane Library, Embase, CNKI, CBM, Wanfang Database, and VIP database were searched for randomized controlled trials (RCTs) of Xiangshao Granules in the treatment of MPS. The search time was from the listing of Xiangshao Granules (2005) to September 1, 2024. Xiangshao granule was used in experimental group. The control group was treated with placebo, other Chinese patent medicine, or conventional western medicine. The treatment period should be at least 4 weeks. RevMan5.4 was used for bias risk assessment and meta-analysis.ResultsA total of 13 randomized controlled trials with 1637 participants were included. The meta-analysis showed that there was statistical significance between Xiangshao granules and control group in improving clinical symptoms (P<0.05). Xiangshao granules could improve the total response rate (OR= 2.78, 95%CI[1.65, 4,68], P<0.05) and reduce Kupperman score (MD=-1.23, 95%CI[-2.10,-0.36], P<0.05). In addition, Xiangshao granules also decreased HAMD score (MD= -2.80, 95%CI[-3.54, -2.07], P<0.05) and HAMA score (MD=-2.52, 95%CI[-3.00,-2.04], P<0.05). In terms of serum hormone levels, there was no significant difference in serum FSH levels between Xiangshao granule group and control group(SMD=-0.81, 95%CI[-2.03, 0.41], P= 0.19). However, the regulating effect of Xiangshao granules on serum LH and E2 levels was statistically significant compared with the control group (P<0.05). The results of subgroup analysis showed that Xiangshao granules were better than other Chinese patent medicines in reducing serum LH levels (SMD=-1.20, 95%C[-1.66,-0.73]I, P<0.05). Xiangshao granules were superior to other Chinese patent medicines or placebo in increasing serum E2 levels (SMD=5.28, 95%CI[4.90, 5.66], P<0.05) (SMD=2.00, 95%CI[1.10, 2.90], P<0.05). Furthermore, the combined use of western medicine and Xiangshao granules was better than HRT or SSRIs alone in reducing serum LH level and increasing serum E2 level (P<0.05). In terms of safety, there was no significant difference in the incidence of adverse reactions among all groups (OR= 1.28, 95%CI[0.80, 2.05], P = 0.31).ConclusionXiangshao Granules can effectively relieve the clinical symptoms of MPS patients, improve the scores of anxiety and depression and regulate the level of serum estrogen, with good safety, and is an ideal treatment plan. In the future, multi-center and large sample randomized controlled trials can be conducted for more key clinical indicators to comprehensively analyze the clinical efficacy and applicability of Xiangshao granules in the treatment of MPS.Systematic review registrationhttps://www.crd.york.ac.uk/, identifier CRD42023405228.